Meeting report: the 5th International expert symposium in Fukushima on radiation and health. Issue 1 (December 2017) - Saenko, Vladimir; Thomas, Geraldine; Yamashita, Shunichi
Abstract Background The symposium entitled "Chernobyl +30, Fukushima +5: Lessons and Solutions for Fukushima's Thyroid Question" was held in September, 2016 in Fukushima. The aim of the Symposium was to revisit and recapitulate evidence from the studies in Chernobyl in order to share multidisciplinary opinions and views on the likely reason for the high rate of thyroid cancer detected by the Thyroid Ultrasound Examination program in Fukushima Prefecture. Participants and matters discussed The high prevalence of thyroid cancer in young individuals causes concerns among Fukushima residents and the general public that it might be due to putative radiation exposure from the Fukushima Daiichi Nuclear Power Plant accident. Twenty-six experts from Japan and abroad, including participants affiliated with international organizations, reviewed the results of radiation epidemiology investigations in Chernobyl, presented clinical experience of diagnosis, treatment and follow-up of patients with radiation-related thyroid cancer, and scrutinized the findings on thyroid cancer in Fukushima. Conclusion Conclusions drawn at the symposium included understanding that in contrast to Chernobyl, doses to the public from the accident in Fukushima were too low to give rise to a discernible excess risk for thyroid cancer. The high detection rate of thyroid cancer and benign abnormalities resulted from the use of highly sensitive ultrasound equipment and sophisticated protocol of examination used in the Thyroid Ultrasound Examination, and therefore not attributable to radiation. Coordinated efforts will be necessary to avoid overdiagnosis and overtreatment, which may carry its own health disbenefits. Clear communication to the screening participants and their families is recommended in regard to why the examination is being conducted and to explain the likely outcomes and risks, including the means and options for treatment if a thyroid disorder is detected.